A CRITICAL STUDY ON THE CONTROVERSY OF ABHIDHAMMA ACCORDING TO HISTORICAL AND TRADITIONAL APPROACH - Medhacitto, Tri Saputra (Jurnal Agama Buddha dan Ilmu Pengetahuan, 2024)
ABSTRACT This research provides a critical examination over the controversy surrounding the history of Abhidhamma based on historical background and written tradition. It is a library research which was done by collecting and scrutinizing data from the Tipitaka and its commentaries, combined with articles and books written by Buddhist scholars. Abhidhamma which is traditionally understood as higher teaching taught by the Buddha, reveals controversies among Buddhist scholars. They questioned the historical authenticity of Abhidhamma as the words of the Buddha, since they found several incompatibilities when looking at the historical background of the development of Buddhist literature. Kathāvatthuppakaraṇa, one of the seven books of Abhidhamma Piṭaka, is strong evidence that the book was compiled by Ven. Mogaliputtatissa Thera in the end of the third Buddhist council long after the parinibbāna of the Buddha. However, the written tradition as reported in the commentaries asserts that Abhidhamma should be accepted as Buddhavacana. Bhikkhu Buddhaghosa Thera in his commentaries consistently tried to highlight the Abhidhamma as higher teachings that should be acknowledged as Buddhavacana. This research sheds light on how the history of Abhidhamma is perceived on through the lenses of history and written tradition.